2011
DOI: 10.1108/13555851111120452
|View full text |Cite
|
Sign up to set email alerts
|

The effects of respect and rapport on relationship quality perception of customers of small healthcare firms

Abstract: PurposeConsequent upon the intense competitive nature of today's business environment, service businesses are seeking for the most creative but effective means of attracting and retaining customers. One of the ways is to build quality relationship via interpersonal relationship with customers. The purpose of this paper is to evaluate two ways of building interpersonal relationship with customers – respect and rapport, and their impact on overall customer perceived relationship quality, as well as the role of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The use of relationship marketing validates trustworthy behavior between supplier and purchaser in successful partnership [45]. Marketing experts link building respect and rapport as successful strategies for developing relationships with customers [44]. A review of marketing research literature includes customer commitment and trust as two important factors in building relationships with customers [46].…”
Section: Customer Service Philosophymentioning
confidence: 93%
See 2 more Smart Citations
“…The use of relationship marketing validates trustworthy behavior between supplier and purchaser in successful partnership [45]. Marketing experts link building respect and rapport as successful strategies for developing relationships with customers [44]. A review of marketing research literature includes customer commitment and trust as two important factors in building relationships with customers [46].…”
Section: Customer Service Philosophymentioning
confidence: 93%
“…Shahraki (2014) [43] indicated that organizational decisions makers must realize the essential requirement in developing organizational goals is customer satisfaction through building trust and relationships with customers. Establishing relationships with customers is the most cost-effective way for organizational decision making to maintain a high level of customer loyalty [44]. The use of relationship marketing validates trustworthy behavior between supplier and purchaser in successful partnership [45].…”
Section: Customer Service Philosophymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore [ 54 ], conducted research in the context of dental clinics in Malaysia, investigating the impact of rapport on relationship quality. Their findings reveal a positive influence of rapport on the overall quality of the relationship between dental service providers and patients [ 12 ].…”
Section: Conceptual Model and Hypothesismentioning
confidence: 99%
“…Yee, Lee, Yeung & Cheng [2] and Zeithaml & Bitner [3] identified that organisations that focused on customer satisfaction were able to build loyal clients who then served to promote the organisations further through vital word-of-mouth advertising referrals. Correspondingly, empirical studies have found a correlation between high quality service encounters and organisations' success and survival in the healthcare sector [4] [5]. In developed countries, healthcare centres have been increasingly using higher quality customer service to satisfy their patients [6]- [8].…”
Section: Introductionmentioning
confidence: 99%